GREASE OR SAND THE WHEEL? THE EFFECT OF INDIVIDUAL BRIBES ON THE DRIVERS OF AGGREGATE PRODUCTIVITY GROWTH - Hanoteau, Julien; Vial, Virginie (Journal of Indonesian Economy and Business, 2014)
The Asian paradox suggests a net grease-the-wheel effect of corruption. Under the assumptionof diminishing returns to bribes, going beyond the single-representative-firm assumption,we argue that the grease and sand-the-wheel effects are likely to co-exist among a large numberof firms, and that the industrial effect of corruption depends on the productivity drivers that fuelfirmâs dynamics. We decompose Indonesian manufacturing labor productivity growth whilecontrasting and comparing the contributions of no-, low- and high-bribing firms over the period1975-94. We confirm the coexistence of grease and sand-the-wheel effects. Industrial productivitygains stem first from the net entry of non-corrupted firms, evidencing a sand-the-wheeleffect. Market share reallocation from low to high productivity growth incumbents paying lowbribes is the second source of productivity growth, pointing at a grease-the-wheel effect. Intraplantproductivity growth is overall negative and largely attributable to high-corruption plants,suggesting a sand-the-wheel effect.Keywords: corruption, bribery, productivity